THE SECURITY OF THE NORDIC STATES UNDER THE RUSSIAN HYBRID THREATS - СТОРОЖИНЕЦЬКИЙ, Тарас (Київський національний університет імені Т. Шевченка, 2025)
Abstract Introduction. The Russian Federation’s full-scale invasion of Ukraine in 2022 marked a critical turning point in the European security landscape, prompting Sweden and Finland to abandon their longstanding policies of neutrality in favor of accession to the North Atlantic Treaty Organization (NATO). This strategic realignment has been accompanied by a notable intensification of Russian hybrid activity in Northern Europe. The resulting transformation of the regional security status quo presents NATO with novel challenges, underscoring the imperative for enhanced coordination mechanisms and deeper integration of the Nordic states into the Alliance’s strategic framework. Methods. The study employs a functional analysis to assess the implications of Russian hybrid operations for the Northern European states, a comparative method to synthesize and contrast the existing scholarly interpretations, and an examination of open-source materials and statistical data to construct an empirical basis for evaluating the scope and impact of Russian hybrid influence in the region. Results. The analysis delineates the evolving patterns and strategic objectives of Russian hybrid activities in Northern Europe following Sweden’s and Finland’s NATO accession. It further evaluates the Nordic states’ role in reinforcing the security architecture of NATO’s northeastern flank and identifies the key domains of vulnerability and potential countermeasures, with particular emphasis on the Baltic Sea region. Conclusions. The escalation of Russian hybrid warfare in Northern Europe post-2022 is not merely a reactive measure to geopolitical shifts but constitutes a calculated element of a broader long-term strategy aimed at undermining the Euro-Atlantic unity and degrading the collective defense capacity of NATO. The study finds that Russian hybrid operations seek to erode the political and military readiness of Nordic states, foster gradual regional destabilization, and weaken the cohesion of the transatlantic alliance. Instruments employed in such strategy include the critical undersea infrastructure sabotage, electoral interference, migration crises orchestration, disinformation campaigns, and the GPS signals jamming.

Анотація Вступ. Повномасштабне вторгнення Російської Федерації в Україну у 2022 р. стало каталізатором для Швеції та Фінляндії у відмові від традиційної політики нейтралітету й приєднанні до Північноатлантичного Альянсу (НАТО). Цей крок викликав посилення гібридної активності РФ у регіоні Північної Європи. Трансформація безпекового статусу-кво створює нові виклики для Альянсу, що зумовлює потребу в розробці спільних механізмів реагування та поглибленні інтеграції нордичних країн. Методи. У дослідженні застосовано функціональний аналіз для визначення впливу гібридних операцій РФ на країни Північної Європи, порівняльний метод — для зіставлення підходів у науковому дискурсі, а також аналіз відкритих джерел і статистичних даних з метою емпіричної оцінки гібридного впливу Росії на держави регіону. Результати. Визначено динаміку та цілі російських гібридних дій у Північній Європі в контексті вступу Швеції та Фінляндії до НАТО. Проаналізовано роль нордичних країн у зміцненні безпеки північно-східного флангу Альянсу, а також окреслено напрями протидії новим викликам, зокрема в акваторії Балтійського моря. Висновки. Активізація гібридної війни Російської Федерації у Північній Європі після 2022 р. є не лише реакцією на зміни в безпековій архітектурі Європи, але й елементом довгострокової стратегії, спрямованої на підрив єдності західних союзників та обмеження їхньої здатності до колективної оборони. Аналіз демонструє, що російська гібридна політика в Північній Європі спрямована на зниження рівня готовності нордичних держав до захисту державного суверенітету, створення умов для поступової дестабілізації держав регіону та ослаблення єдності євроатлантичного простору. У цьому контексті Росія використовує широкий спектр інструментів: диверсії проти підводної інфраструктури, втручання у виборчі процеси, ініціювання міграційних криз, дезінформаційні кампанії та глушіння сигналів GPS.
БЕЗПЕКА НОРДИЧНИХ КРАЇН В УМОВАХ РОСІЙСЬКИХ ГІБРИДНИХ ЗАГРОЗ
Keywords: нордичні країни; Північна Європа; регіональна система міжнародних відносин; зовнішньополітична стратегія; регіональна безпека; гібридна війна; державний суверенітет.; Нордичні держави; Північна Європа; НАТО; Регіональна безпека; Гібридна війна; Nordic countries; Northern Europe; regional system of international relations; foreign policy strategy; regional security; hybrid warfare; state sovereignty.; Nordic countries; Northern Europe; NATO; Regional security; Hybrid warfare.